2012
DOI: 10.5194/acp-12-2459-2012
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols-cloud microphysics-thermodynamics-turbulence: evaluating supersaturation in a marine stratocumulus cloud

Abstract: Abstract. This work presents a unique combination of aerosol, cloud microphysical, thermodynamic and turbulence variables to characterize supersaturation fluctuations in a turbulent marine stratocumulus (SC) layer. The analysis is based on observations with the helicopter-borne measurement platform ACTOS and a detailed cloud microphysical parcel model following three different approaches: (1) From the comparison of aerosol number size distributions inside and below the SC layer, the number of activated particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 22 publications
5
69
0
Order By: Relevance
“…The two measurement locations discussed here are interesting with regard to the ratio of presumed cloud droplet number concentration (CDNC) to the total aerosol particle number concentration. It has been reported that, although under the clean and convective conditions ambient S c may reach as high as 1.0 %, in the polluted boundary layer S c usually remains below 0.3 % (Ditas et al, 2012;Hammer et al, 2014;Hudson and Noble, 2014). If one assumes this value, a comparatively small fraction of aerosol in northern Finland and central Netherlands would potentially activate into cloud droplets if exposed to this S c .…”
Section: Ccn Concentrationsmentioning
confidence: 99%
“…The two measurement locations discussed here are interesting with regard to the ratio of presumed cloud droplet number concentration (CDNC) to the total aerosol particle number concentration. It has been reported that, although under the clean and convective conditions ambient S c may reach as high as 1.0 %, in the polluted boundary layer S c usually remains below 0.3 % (Ditas et al, 2012;Hammer et al, 2014;Hudson and Noble, 2014). If one assumes this value, a comparatively small fraction of aerosol in northern Finland and central Netherlands would potentially activate into cloud droplets if exposed to this S c .…”
Section: Ccn Concentrationsmentioning
confidence: 99%
“…Another method to derive the supersaturation of a cloud was used by, for example, Hammer et al (2014), Ditas et al (2012), Asmi et al (2012), and Anttila et al (2009). In these studies the fraction of activated particles in a cloud was deduced from the comparison of the number size distribution of interstitial particles (i.e., particles not taken up into cloud droplets) and total aerosol particles (i.e., cloud residuals plus interstitial particles).…”
Section: L Krüger Et Al: Assessment Of Cloud Supersaturationmentioning
confidence: 99%
“…A common approach to derive an effective average peak supersaturation at which ambient clouds are formed is to compare the particle number or CN size distributions of total and interstitial aerosol (e.g., Anttila et al, 2009; al., 2012; Ditas et al, 2012;Hammer et al, 2014). We also used this method, which will be referred to as the "SMPS method", to calculate S avg from our aerosol size distribution measurement results.…”
Section: Average Peak Supersaturation Based On 50 % Activation S Avgmentioning
confidence: 99%
“…These values are chosen based on observations that updrafts in stratocumulus clouds are in the order of 0.1 m s −1 and in cumulus clouds are in the order of 1.0 m s −1 (Ditas et al, 2012;Katzwinkel et al, 2014). Results also show that they correspond to the aerosollimited regime (the 1.0 m s −1 case leads to a w/n ratio of 10 −3 m s −1 cm 3 ) and the transitional regime (the 0.1 m s −1 case leads to a w/n ratio of 5 × 10 −4 m s −1 cm 3 ).…”
Section: Effect Of Vertical Velocitymentioning
confidence: 99%
“…Turbulence induces vertical oscillations of air parcels and causes fluctuations in temperature, water vapor concentration and supersaturation (e.g., Ditas et al, 2012;Hammer et al, 2015). The effects of supersaturation fluctuations on droplet condensational growth in turbulent environments have been studied for several decades (e.g., Cooper, 1989;Khvorostyanov and Curry, 1999).…”
mentioning
confidence: 99%